Pemerolehan Bahasa Anak Usia 2 Tahun (Studi Kasus Syakira Fiola Zahwa) Garuda Sakti Km 2 Kecamatan Tampan Pekanbaru Riau - Pratiwi, Yolanda; Herwandi, Herwandi (UIR PRESS, 2021)
Language is a means of communication acquired by humans from birth. At the beginning of the baby is born, does not yet have the ability to talk to other people. Mastery of language by children begins with the acquisition of the first language, namely the mother tongue. However, there is a deliberate factor from parents in stimulating language that is not in accordance with the proper sound of the language. In addition, there is a factor in the difficulty of children in imitating the language of their parents. The aims of this study are to: (1) describe, analyze and interpret the form of changes in language sounds that occur in language acquisition in children aged 2 years (2) describe, analyze and interpret the factors that cause changes in language sounds in language acquisition that occur in Syakira Fiola Zahwa . The data that has been collected will be described, analyzed, and interpreted in detail and systematically so that it can be seen the form of changes and factors that cause changes in the sound of language in Syakira Fiola Zahwa. The method used in this research is descriptive method. The research approach used in this study is a qualitative approach. The data collection techniques in this study were observation, interviews, listening to the conversation, fishing, taking notes, and recording. The results of this study indicate that: (1) The form of changes in language sounds that occur in the language of children aged 2 years in the language acquisition process consists of; (a) changes in the sound of language that occur due to the failure of the child to suppress a process. (b) changes that occur as a result of generalizations, (c) changes in the sound of language due to the irregularities of the conscience processes. (2) Factors of Changes in Language Sounds That Occur in the Language of 2-Year-Old Children in Language Acquisition consist of: (a) changes in language sounds that occur due to intentional factors from parents, (b) sound changes that occur due to factors that a child experiences difficulties when imitating the voices of their parents. This shows that there are 3 forms of changes in the sound of language in children aged 2 years (Syakira Fiola Zahwa) which are influenced by 2 factors, namely the intentionality of parents and the difficulty of children imitating the sounds of their parents' speech.